The Statutes at Large of the State of Minnesota: Comprising the General Statutes of 1866 as Amended by Subsequent Legislation to the Close of the Session of 1873: Together with All Laws of a General Nature in Force, March 7, A.D. 1873 with References to Judicial Decisions of the State of Minnesota, and of Other States Whose Statutes are Similar to Which are Prefixed the Constitution of the United States, the Organic Act, the Act Authorizing a State Government, and the Constitution of the State of Minnesota, at 993 (Vol. 2, 1873), Of Crimes and Their Punishment, Setting Spring Guns Unlawful, § 64-65 - (:unkn) unknown (General Publisher, 1873)
Prohibtied the setting of any trap gun, spring gun, or putting a pistol, rifle, or other deadly weapon "in this state." . Punished by imprisonment for at least 6 months or a fine of up to $500 if no injury results; imprisonment for up to 5 years if non-fatal injury results; and imprisonment for 10-15 years if death results.
--
Keywords: TRAP GUNS